THE ROLE OF GROWTH FACTORS IN THE DEVELOPMENT OF LEFT VENTRICULAR DIASTOLIC DYSFUNCTION IN PATIENTS WITH ARTERIAL HYPERTENSION AND TYPE 2 DIABETES MELLITUS - Rieznik, L.А.; Starchenko, Т.G.; Koval, S.N.; Shkapo, V.L. (World of Medicine and Biology, 2023)
The role of insulin-like growth factor-1 and transforming growth factor-β1 in the pathogenetic mechanisms of the formation of diastolic dysfunction of the left ventricle of the heart in patients with arterial hypertension and with type 2 diabetes mellitus were studied. 67 patients with type 2 diabetes mellitus and 46 with arterial hypertension and without diabetes mellitus patients were examined. Patients with arterial hypertension with concomitant diabetes mellitus were more marked than the diastolic function of the left ventricle. The relationship between the level of the transforming growth factor-β1 and the diastolic function of the left ventricle is established. In the presence of signs of diastolic dysfunction, the level of this growth factor was significantly higher in both groups of patients. The relationship between the level of insulin-like growth factor-1 and the indicators of diastolic function of the heart has not been established.
Keywords: arterial hypertension; diabetes mellitus type 2; diastolic function of the left ventricle; insulin-like growth factor-1; transforming growth factor-β1